Haemophilia Carriers Experience Study (CARES): A mixed method exploration into the experience of women who are carriers of Haemophilia. Issue 5 (19th June 2021) - Whitaker, Sarah; Aiston, Helen; Hung, Wai Tung; Pink, Ruth; Mangles, Sarah
Abstract: Introduction: Haemophilia research has traditionally focused on patients diagnosed with haemophilia and although research priorities are rapidly changing, there is still a lot more we need to understand about the experiences and psychosocial issues facing women who are diagnosed as carriers of haemophilia ( Haemophilia, https://doi.org/10.1111/hae.14043 ). One study noted that the understanding of carriers' experience of bleeding by healthcare professionals is limited and that many women have had negative experiences of healthcare ( Haemophilia, 17, 2011, 237). The carrier population does not typically receive much support for themselves as individuals as they are often not registered at Haemophilia Centres in their own right. Aim: This study aimed to look at the emotional wellbeing of carriers in more detail. Method: This was initially investigated through the use of focus groups and individual interviews with 16 participants (Stage 1) and then widening the study using an online questionnaire battery developed from the themes identified from these interviews (Stage 2). The questionnaire battery was completed by 226 participants. Results: Descriptive statistics are reported on the endorsement of themes identified in Stage 1 and around participants' experiences of their carriership and healthcare. Results demonstrated that the participants have had a number of difficulties with accessing helpful information and support during key times in their lives, for example, at diagnosis and when deciding whether to start a family. They also showed that although participants endorsing a higher number of bleeding symptoms scored statistically significantly higher in measures of depression, anxiety and negative affect, this difference was not clinically significant. Conclusion: These results lend support to the growing evidence base that women who are carriers of haemophilia have a distinct set of (currently unmet) needs that need assessing and treating.